Pencegahan Kekerasan Fisik Terhadap Istri Oleh Suami (Studi Kasus Pada Polresta Pulau Ambon Dan Pulau-Pulau Lease) - Stevano G Lekatompessy; Margie Gladies Sopacua; Iqbal Taufik (PATTIMURA Law Study Review, 2023)
Domestic violence, especially against wives, is a frequent legal action. The occurrence of several acts of domestic violence, especially against wives, can be said to be a victim. Related to violence against women is in the private or personal sphere, namely Relationships and Personal Domestic Violence at 79% (6,480 cases). Among others, there is violence against wives (KTI) with the first position of 3,221 cases (49%).Conclusion This study aims to examine and discuss the factors that cause husbands to commit physical violence against their wives, and also to examine and discuss efforts to prevent domestic violence so that husbands do not commit acts of physical violence against their wives. The research method used is empirical juridical with descriptive analytical type of research, legal data collection techniques, namely primary data and secondary data and analysis techniques using descriptive-qualitative. This analysis is a method of analyzing data that can be in the form of sentences or words that are carried out by analyzing, describing, interpreting, and presenting written or oral data based on its grouping, the purpose of which is to make the data more accurate.Victims; (2) Preventing domestic violence; (3) Submitting an application for a protection determination; and (4) Providing emergency assistance Factors causing husbands to act physically violent towards their wives include; (1) Domination Factors; (2) Psychological Factors; (3) Economic Factors; (4) Infidelity Factors, (5) Fatigue Factors; and (6) Environmental Factors. Efforts to prevent domestic violence so that husbands do not act physically violent to their wives include (1) Practicing religious teachings; (2) Communication; (3) Early education; (4) mediation; and (5) Legal Counseling or Socialization. In addition to the government, in the PKDRT Law there are also community obligations, where each individual who knows, hears.